Psychological peculiarities in children with the autistic spectrum disorder - KACHMARYK, KHRYSTYNA (Journal of Education Culture and Society, 2020)
The psychological peculiarities of symptom occurrence in children with autistic spec-trum disorder are outlined in this article. The views of different authors on this topic were analyzed and the direct correlation connections between the separate symptom occurren-ces were described in the article. A qualitative analysis of autistic disorder appearance in children with different levels of autism was conducted.